Cotton Production in Kansas - Duncan, Stewart R.; Fjell, Dale L.; Peterson, Dallas E.; Warmann Gerald W. (My University, 1993)
This publication provides general information on cotton production practices that may be helpful to Kansas farmers interested in this crop.
MF1088_1993-10
Keywords: MF1088; Crops; Economics; MF